GREAT RENEWALS IN THE PHANEROZOIC HISTORY OF THE EARTH - Solov'yev V.O. (My University, 1988)
Geologists have repeatedly formulated ideas concerning great renewals of short duration in the Precambrian history of the Earth, i.e., colossal structural reorganizations, collapses, extensive inversions and changes in type of tectogenesis, lithogenesis and igneous activity. For the Phanerozoic, there are considerably fewer such generalizations and formulations. By analyzing its comparatively accurately dated sedimentary and igneous rocks we demonstrate the possibility of contemporaneous planetary reorganizations and their specific durations. Various well-known regional sedimentary paleogeographic, tectonic and magmatic changes seem to have been contemporaneous in structurally very diverse regions of the world, and therefore, can be regarded as continental or even global. The most significant Phanerozoic boundary probably was the Visean, which was marked by extensive changes in sedimentation conditions.
Keywords: Precambrian; Visean; Paleozoic::Carboniferous::Mississippian::Middle::Visean; Precambrian; Палеозой::Каменноугольная::Средний::Визейский; Докембрий